Insights Into the Role of Mortalin in Alzheimer’s Disease, Parkinson’s Disease, and HIV-1-Associated Neurocognitive Disorders - Priyanka,; Seth, Pankaj (Frontiers in Cell and Developmental Biology, 2022)
Mortalin is a chaperone protein that regulates physiological functions of cells. Its multifactorial role allows cells to survive pathological conditions. Pharmacological, chemical, and siRNA-mediated downregulation of mortalin increases oxidative stress, mitochondrial dysfunction leading to unregulated inflammation. In addition to its well-characterized function in controlling oxidative stress, mitochondrial health, and maintaining physiological balance, recent evidence from human brain autopsies and cell culture–based studies suggests a critical role of mortalin in attenuating the damage seen in several neurodegenerative diseases. Overexpression of mortalin provides an important line of defense against accumulated proteins, inflammation, and neuronal loss, a key characteristic feature observed in neurodegeneration. Neurodegenerative diseases are a group of progressive disorders, sharing pathological features in Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, and HIV-associated neurocognitive disorder. Aggregation of insoluble amyloid beta-proteins and neurofibrillary tangles in Alzheimer’s disease are among the leading cause of neuropathology in the brain. Parkinson’s disease is characterized by the degeneration of dopamine neurons in substantia nigra pars compacta. A substantial synaptic loss leading to cognitive decline is the hallmark of HIV-associated neurocognitive disorder (HAND). Brain autopsies and cell culture studies showed reduced expression of mortalin in Alzheimer’s, Parkinson’s, and HAND cases and deciphered the important role of mortalin in brain cells. Here, we discuss mortalin and its regulation and describe how neurotoxic conditions alter the expression of mortalin and modulate its functions. In addition, we also review the neuroprotective role of mortalin under neuropathological conditions. This knowledge showcases the importance of mortalin in diverse brain functions and offers new opportunities for the development of therapeutic targets that can modulate the expression of mortalin using chemical compounds.